2015
DOI: 10.1103/physrevb.92.045427
|View full text |Cite
|
Sign up to set email alerts
|

Transport through graphenelike flakes with intrinsic spin-orbit interactions

Abstract: It was shown recently [J. L. Lado and J. Fernández-Rossier, Phys. Rev. Lett. 113, 027203 (2014)] that edge magnetic moments in graphene-like nanoribbons are strongly influenced by the intrinsic spin-orbit interaction. Due to this interaction an anisotropy comes about which makes the in-plane arrangement of magnetic moments energetically more favorable than that corresponding to the out-of-plane configuration. In this paper we raise both the edge magnetism problem and the differential conductance and shot noise… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…It has been shown earlier [3,4,8] and confirmed experimentally [9,10] that graphene-like nanoribbons and nanoflakes get spontaneous magnetization at zigzag edges (even at room temperature). It has also been shown that usually the in-plane magnetic configuration is energetically more favourable than the out-of-plane one.…”
Section: Discussion Of the Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…It has been shown earlier [3,4,8] and confirmed experimentally [9,10] that graphene-like nanoribbons and nanoflakes get spontaneous magnetization at zigzag edges (even at room temperature). It has also been shown that usually the in-plane magnetic configuration is energetically more favourable than the out-of-plane one.…”
Section: Discussion Of the Resultsmentioning
confidence: 73%
“…The model which has been proved to provide a good description of graphene-like nanostructures reads as follows (see [3,4] and references therein)…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical studies of graphenelike nanoribbons are usually carried out for the out-of-plane configuration [18 and 19], but it is now known that the in-plane configuration is often energetically the most stable one [20][21][22]. Here most of our attention is directed to this very configuration which constitutes the ground state for energies close to the charge neutrality point (CNP).…”
Section: Electronic Band Structure and Edge Magnetic Momentsmentioning
confidence: 99%
“…The problem is exactly solved by a direct diagonalization of the full Hamiltonian (cf. [5,6]). Figure 1 shows a distribution of magnetic moments in a small rectangular GLNR composed of W ac = 6 zigzag lines (width),and L zz = 8 blunt saw-teeth lines (length), the last line is incomplete for symmetry reasons.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike graphene, they usually have sufficiently large intrinsic spin-orbit interaction which strongly impacts their electronic and magnetic properties [1][2][3]. It is now known that zigzag-shaped edges of graphene and graphene-like nanoribbons (GLNRs) may have noticeable magnetic moments, and their ground state configuration corresponds to the in-plane spin arrangement rather than the out-of-plane one [4,5]. The aim of this study is to estimate the effect of both ISOI and perpendicular external electric field on energy gaps and edge magnetic moments of GLNR.…”
Section: Introductionmentioning
confidence: 99%